Puritans and Catholics in the Trans-Atlantic World 1600–1800 - Gribben, Crawford; Spurlock, R. Scott (Christianities in the Trans-Atlantic World, 1500–1800, 2015)
This volume explores the complex and surprisingly similar experiences of puritans and Catholics in the early modern Atlantic world.